The Analysis of Students’ Motivation and the TOEFL Preparation Class in Relation to Their Predicted TOEFL Scores - Mardiyah, Mutmainatul (Candradimuka: Journal of Education, 2024)
The achievement of high predicted TOEFL scores by students is not easily obtained without strong motivation and thorough preparation from both the students themselves and their environment. The research conducted at FETEC (Faculty of Economics Trisakti English Center) aims to analyze the students' motivation and TOEFL preparation classes in relation to their predicted TOEFL scores. Quantitative research data was collected by distributing questionnaires to 20 respondents as a sample, using Google Forms. Sampling was conducted randomly or through simple random sampling. The collected data was processed according to research procedures and analyzed using multiple linear regression analysis in SPSS 20. The results of this study indicate that students' motivation and TOEFL preparation classes are crucial in achieving high predicted TOEFL scores. This improvement is achieved through various actions and measures, ranging from basic security and social integration to personal achievement and self-fulfillment. It illustrates how different levels of needs—from basic to self-actualization—drive students to take action and enroll in preparation classes to achieve their goals. These actions significantly contribute to the growth of students’ motivation on the achievement of the predicted TOEFL score.  The greater the students' motivation to enroll in TOEFL preparation classes, the higher their predicted TOEFL scores. Attaining high predicted scores satisfies their academic requirements, allowing them to participate in their thesis defense.